Ideal Islamic economy : an introduction - Mirakhor, Abbas ; Askari, Hossein (Palgrave Macmillan, 2020)
This book provides an introduction to the vision of an economic system based completely on the Holy Qur'an--a system defined as a collection of institutions, representing rules of behavior, prescribed by Allah for humans, and the traditions of the Messenger. The authors argue that the main reason for the economic underperformance of Muslim countries and their economies has been non-compliance with the prescribed rules of behavior. Rule non-compliance has been chiefly due to the failure of Muslims to comprehend the Metaframework of the Qur'an and the Archetype Model of the Prophet Mohammad and interpret them in ways compatible with their own generation and time. Askari and Mirakhor believe these rules (institutions), properly adapted to prevailing conditions present what they consider as an ideal economic system.Contents; List of Tables; 1 Introduction; Orientalism and Ersatz Islam; Weber, New-Orientalism and Ersatz Islam; Secularism and the New-Orientalism; Ersatz Islam, "Islamic Law, " Shari'ah, and Islamic Jurisprudence (Fiqh); Ersatz Islam and the Marxist Paradigm54; For Whom the Orientalist Bell Tolls?; References; 2 Capitalism and the Islamic Economic System; Does Capitalism Define an Islamic Economy?; Defining Capitalism; Exchange, Principle and Mentality of Capitalism; Islam and Capitalism-the Connection; Varieties of Capitalism. Contents: Religious Basis of Adam Smith's Vision of the EconomyIslamic Economic System and Capitalism; Does Capitalism Define an Islamic Economy?; References; 3 Overview of an Ideal Islamic System; The Qur'an; The Concept of Barakah; The Objectives and Role of the Prophets and Messengers; The New Institutional Economics and Institutional Scaffolding; Institutional Scaffolding of Ideal Islamic Economy; Role of Rules; Rules of the Metaframework; Overview of Sunan of Allah and Their Characteristics; Overview of Rules Governing Humans' Relation with Allah (swt), with Their Own Self and with One Another. Contents: 7 Contemporary Muslim Economies and Rule ComplianceReferences; 8 Towards Achieving the Ideal Islamic Economy; References; 9 Conclusions; Bibliography; Index.